Regularities of the metallurgical industry restructuring process: Content, safety and regulation - I. D. Matskulyak; V. I. Mysachenko; N. V. Sanin (Вестник университета)
The purpose of the work is to reveal the content, safety and regulation of the metallurgical industry restructuring. The objectives of the article are to generalize the theory and methods that characterize the essence of the designated industry restructuring regularities, the main directions of their safe implementation and regulation. The subject of the publication defines the organizational and economic relations arising during the implementation of the Russian metallurgy safe restructuring. The methodology of the study proceeds from objectively recurring significant relationships and dependencies that arise in the metallurgical industry restructuring process, the main link of its economy. The key results are reduced to determining a number of regularities of restructuring, its essence, features, priorities, clustering and ways of safe regulation by the state. Their scientific understanding is quite applicable both in educational institutions of the country when studying the theory and methodology of economic science, methods of restructuring of various sectors of the economy, and in real practice of structural changes at all levels of government. In conclusion, a number of findings are formed, reflecting both the content and safety of the restructuring of metallurgy and the corresponding laws, and the regulation of these processes.